Feedforward and Feedback Vibration Control and Algorithm Design for Cable-Bridge Structure Nonlinear Systems. (23rd March 2014) - Liang, Yan-Jun; Wu, Shi-Liang; Gao, De-Xin; Xue, Xiao-Rong
Abstract : Technique of feedforward and feedback optimal vibration control and simulation for long-span cable-bridge coupled systems is developed. Buffeting loading systems of long-span cable-bridge structure are constructed by weighted amplitude wave superposition method. Nonlinear model of cable-bridge coupled vibration control system is established and the corresponding system of state space form is described. In order to reduce buffeting loading influence of the wind-induced vibration for the structure and improve the robust performance of the vibration control, based on semiactive vibration control devices and optimal control approach, a feedforward and feedback optimal vibration controller is designed, and an algorithm is presented for the vibration controller. Numerical simulation results are presented to illustrate the effectiveness of the proposed technique.